2012
DOI: 10.1111/j.1365-2486.2011.02625.x
|View full text |Cite
|
Sign up to set email alerts
|

Future wood productivity ofPinus radiatainNewZealand under expected climatic changes

Abstract: The physiologically based growth model CenW was used to simulate wood‐productivity responses of Pinus radiata forests to climate change in New Zealand. The model was tested under current climatic conditions against a comprehensive set of observations from growth plots located throughout the country. Climate change simulations were based on monthly climate change fields of 12 GCMs forced by the SRES B1, A1B and A2 emission scenarios for 2040 and 2090. Simulations used either constant or increasing CO2 concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 66 publications
2
35
0
Order By: Relevance
“…Incorporating the effects of rising CO 2 in models of future tree growth continues to be a major challenge. The sensitivity of projected productivity to assumptions regarding increased CO 2 was high in modelling studies of climate change impacts in commercial timber plantations in the Southern Hemisphere (Kirschbaum et al 2012;Battaglia et al 2009), and a recent analysis indicated a general convergence of different model predictions for future tree species distribution in Europe, with most of the difference between models due to the way in which this effect is incorporated (Cheaib et al 2012). Increased CO 2 has been shown to increase the water-use efficiency of trees, but this is unlikely to entirely offset the effects of increased water stress on tree growth in drying climates (Leuzinger et al 2011;Booth 2013).…”
Section: Ecosystem Responses To Climatementioning
confidence: 99%
“…Incorporating the effects of rising CO 2 in models of future tree growth continues to be a major challenge. The sensitivity of projected productivity to assumptions regarding increased CO 2 was high in modelling studies of climate change impacts in commercial timber plantations in the Southern Hemisphere (Kirschbaum et al 2012;Battaglia et al 2009), and a recent analysis indicated a general convergence of different model predictions for future tree species distribution in Europe, with most of the difference between models due to the way in which this effect is incorporated (Cheaib et al 2012). Increased CO 2 has been shown to increase the water-use efficiency of trees, but this is unlikely to entirely offset the effects of increased water stress on tree growth in drying climates (Leuzinger et al 2011;Booth 2013).…”
Section: Ecosystem Responses To Climatementioning
confidence: 99%
“…In the context of global warming, the effect of rising temperatures on site productivity have been examined and both positive and negative impacts have been reported (Loustau et al 2005, Ollinger et al 2008, Kellomäki et al 2008, Chiang et al 2008, Latta et al 2009, Coops et al 2010, Kirschabum et al 2012. Quantifying such effect is still challenging, because the temperature simultaneously affects ecosystem processes (photosynthesis, respiration, transpiration, allocation, decomposition, etc.).…”
Section: Site Index Response To Climate Changementioning
confidence: 99%
“…Therefore possible changes in water availability due to changes in weather with increasingly erratic seasonal rainfall and more frequent and severe drought events, coupled with increased evaporative demand brought about by higher temperatures have the potential to alter forest growth and reduce primary production (Kirschbaum and Fischlin 1996). At present, soil water deficits are common across many eastern regions of New Zealand during summer (Palmer et al 2009) and many of these areas are predicted to receive less rainfall in the future (Mullen et al 2005;Kirschbaum et al 2012).…”
Section: Introductionmentioning
confidence: 99%